(untitled) (American Journal of Islam and Society, 2014)
There have been few studies on Islam in Canada. Hence this publication is a welcome addition to the list. Its ten chapters, divided into four sections, examine diverse issues regarding Muslim cultural politics in the Canadian hinterlands. More specifically, it seeks to understand how they have been affected by the post-9/11 era of wars, domestic security policies, calls for reformation, and media sensationalism, as well as how these, combined with racial and re- ligious profiling, have impacted Muslims in the Canadian diaspora. The book tries to construct multiple readings of Islam and Muslims by examining this community within its social, cultural, educational, and political settings and the integration of these diverse factors in the formation of the national Islamic mosaic. The first section covers gender, race, the Shari‘ah debate, and Muslim women’s political engagement. Section 2 focusses on media representation and examines the construction of the “Muslim other” post-9/11, the politics of reform as articulated by two Muslim female journalists, and the representation of Canadian Islam in a popular Muslim sitcom. An important theme in section 3 is the civic engagement of the country’s Islamic schools. The last section looks at security issues and the targeting and profiling of Muslims in post-9/11 Canada. As Jasmine Zine correctly points out in the introduction, Muslims have been living peacefully in Canada since the middle of the nineteenth century and are proud to be Canadian. However, since 9/11 the debate on their integration into the mosaic and their appropriation of Canadian values has intensified, especially in Quebec, where discrimination and prejudice have increased due to the issue of veiling. Women who choose to veil are exiled from public services and space by means of Bill 94. In essence they are portrayed as victims of patriarchal violence ...